What Is Success? A Narrative Review of Research Evaluating Outcomes of Antibiotics Used for Treatment of Clinical Mastitis - Ruegg, Pamela L. (Frontiers in Veterinary Science, 2021)
Treatment of clinical mastitis is the most common reason that antimicrobials are given to adult dairy cows and careful consideration of treatment protocols is necessary to ensure responsible antimicrobial stewardship. Clinical mastitis is caused by a variety of bacteria which stimulate an immune response that often results in spontaneous bacteriological clearance but can develop into long-term subclinical infections. Use of antimicrobial therapy is most beneficial for cases that are caused by pathogens that have a low rate of spontaneous cure but high rate of therapeutic cure. The purpose of this paper is to review studies that evaluated outcomes of antimicrobial therapy of clinical mastitis. Few studies reported differences in bacteriological cure among treatments and this outcome was rarely associated with clinical outcomes. Return to normal milk appearance was evaluated in most studies but demonstrated little variation and is not a reliable indicator of therapeutic success. Somatic cell count should be measured at quarter-level and will decline gradually after bacteriological clearance. Few researchers have evaluated important clinical outcomes such as post-treatment milk yield or culling. Few differences among approved antimicrobial therapies have been demonstrated and selection of antimicrobial therapy should consider the spectrum of activity relative to etiology.